THE TRAP OF SUCCESS AND THE CHALLENGES OF MANAGEMENT IN A NEW CONTEXT: The Case of Espaço Saúde Store - Gonçalves, Alexandre Honig; Lima Novais, Renato (Encontro Internacional de Gestão, Desenvolvimento e Inovação (EIGEDIN), 2026)
This paper addresses the critical adaptation needs of a company in the face of a global scenario of constant structural changes and high competitiveness. The text presents a case study of the "Espaço Saúde" store, a micro-enterprise in the natural products sector, located in Nova Andradina, Mato Grosso do Sul. The study describes how this company, with the support of SEBRAE MS through the ALI Productivity Program, implemented a set of practical solutions to optimize its management. The main actions included the professionalization of digital marketing with a focus on educational content; training of the sales team; and the formation of a strategic partnership. As an objective consequence, the store has been differentiating itself in the local market and also achieving growth in its gross revenue and productivity index, demonstrating how action oriented towards synergistic solutions builds good results.